ChIP-seq identifies McSLC35E2 as a novel target gene of McNrf2 in Mytilus coruscus, highlighting its role in the regulation of oxidative stress response in marine mollusks - Qiu, Longmei; Chen, Xinglu; Zhu, Li; Yao, Ronghui; Qi, Pengzhi (Frontiers in Physiology, 2023)
NF-E2-related factor 2 (Nrf2) plays a crucial role in the oxidative regulatory process, which could trigger hundreds of antioxidant elements to confront xenobiotics. In the previous study, we identified Nrf2 from the marine mussel Mytilus coruscus, and the findings demonstrated that McNrf2 effectively protected the mussels against oxidative stress induced by benzopyrene (Bap). In order to delve deeper into the underlying mechanism, we utilized Chromatin Immunoprecipitation followed by sequencing (ChIP-seq) technology to systematically identify potential novel target genes of McNrf2. A total of 3465 potential target genes were screened, of which 219 owned binding sites located within the promoter region. During subsequent experimental verification, it was found that McSLC35E2, a candidate target gene of McNrf2, exhibited negative regulation by McNrf2, as confirmed through dual luciferase and qRT-PCR detection. Further, the enzyme activity tests demonstrated that McNrf2 could counteract Bap induced oxidative stress by inhibiting McSLC35E2. The current study provides valuable insights into the application of ChIP-seq technology in the research of marine mollusks, advancing our understanding of the key role of Nrf2 in antioxidant defense mechanisms, and highlighting the significance of SLC35E2 in the highly sophisticated regulation of oxidative stress response in marine invertebrates.